Energy issues of bike sharing systems: from energy harvesting to contactless battery charging - Matias, Ricardo
Bicycles (from bike sharing systems) are being introduced in cities as a clean, flexible, inexpensive shared personal mobility vehicle. New features were and are under development on smartBikeEmotion project: automatic location, authentication and locking/unlocking, healthcare capabilities, information services, electric motion assistance, etc.. Entitled as smart bicycle, this vehicles battery is being planned to be charged through energy harvesting solutions when in use or parked outside docking stations, or through an high power source when at the docking stations or during transportation. In these last two situations, the charging process may rely on contactless instead of galvanic contact charging, however, the non-invasive magnetic connection improves electric and mechanic reliability. Nowadays, there are wireless power transfer low cost solutions available for mobile devices, high cost solutions for electric vehicles like buses and cars, and there is a gap in the middle for solutions to apply in bicycles for example. In this paper, we propose a low cost contactless power transfer scheme based on a modification of a flyback configuration, that is described and circuit simulated. It uses a minimal number of components and thus, permits contactless battery charging with extreme simplicity and good efficiency.